Patient right to pastoral service during hospitalization - Wroński, Konrad (Contemporary Oncology/Współczesna Onkologia, 2007)
One of the basic patients’ right is the right to pastoral service during hospital stay. Managers of medical outposts have legal obligation to provide patients with a possibility to participate in religious ceremonies and contact with their chaplain in the hospital. The following article presents legal aspects related to pastoral service of patients in the hospital.